2005
DOI: 10.1002/csr.81
|View full text |Cite
|
Sign up to set email alerts
|

Risk management in sustainable supply chain management (SSCM): lessons learnt from the case of GMO‐free soybeans

Abstract: A well designed risk-oriented supply chain management can put companies in a privileged position to deliver sustainable and reliable long-term benefits to all stakeholders in the value chain. The case of GMO-free soybean supply illustrates the various aspects of risk prevention that can lead to a systematic model of sustainable supply chain management. The article illustrates how -after consumers pressed the food industry to exclude GMO soybeans from their products -a sustainable soybean supply chain was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 3 publications
0
61
1
6
Order By: Relevance
“…Sustainable supply chain management can enhance the competitiveness of enterprises, by putting pressure on those companies that do not implement sustainable supply chain management in a given industry [29,30]. Yalabik and Fairchild found that sustainable supply chain management found consensus among competitors whose companies were forced to implement sustainable supply chain management practices [31].…”
Section: Industry Pressure and Sustainable Supply Chain Managementmentioning
confidence: 99%
“…Sustainable supply chain management can enhance the competitiveness of enterprises, by putting pressure on those companies that do not implement sustainable supply chain management in a given industry [29,30]. Yalabik and Fairchild found that sustainable supply chain management found consensus among competitors whose companies were forced to implement sustainable supply chain management practices [31].…”
Section: Industry Pressure and Sustainable Supply Chain Managementmentioning
confidence: 99%
“…A well designed, risk-oriented supply chain provides a strong competitive position and reliable long-term benefits to all stakeholders [6]. For SCRM to be most effective, it should be integrated with ERM.…”
Section: Introductionmentioning
confidence: 99%
“…Tedarik zinciri yönetimi yazınında çocuk işçiliği, güvenli olmayan çalışma koşulları gibi sosyal konulara da değinilmiştir 30 . Kurumsal sorumluluk, çalışanların profesyonel gelişimi ve etik çalışma gibi başlıklar da sürdürülebilirliğin sosyal boyutunda ele alınmaktadır 31 .…”
Section: üçLü Bilanço Yaklaşımı (Triple Bottom Line/tbl)unclassified